A New Situation Analysis in Environmental Literacy: Microplastic Waste Awareness - Çankaya, İbrahim and Çankaya, Nevin (Technium Education and Humanities, 2025)
The aim of this study is to compare the microplastic awareness levels of pre-service teachers from different branches. The study was conducted with a general survey design, one of the quantitative research methods. The study group consisted of students enrolled in the teaching formation certificate program at Uşak University in the spring semester of 2025. The “Microplastic Awareness” test used in the study was developed by Sandalcı. It was determined that pre-service teachers’ awareness of microplastics was at a low level. There was no significant difference between the microplastic awareness scores of pre-service teachers in the fields of science and health sciences. It was determined that there was a significant difference between the awareness scores of female pre-service teachers and the mean scores of male pre-service teachers in the dimension of the ways microplastics are found in nature. It was determined that there was a significant difference between the mean scores of pre-service science teachers and pre-service health sciences teachers in the dimension of the way microplastics are found in nature. In order to increase the awareness of pre-service teachers about microplastics, there should be a microplastics course in all associate and undergraduate programs at universities. Under awareness projects at universities; conferences, seminars, teleconferences, e-seminars, digital exhibitions and environmental trips can be organized to raise awareness on microplastics.